Mycobacterium xenopi systemic infection in a domestic fiery-shouldered conure bird (Pyrrhura egregia). (4th July 2018) - St-Jean, Guillaume; Gagnon, Carl A.; Soualhine, Hafid; Tremblay, Manon; Beaulieu, Andrée-Anne; Sylvestre, Doris
Abstract : Introduction. Mycobacterium xenopi is a rare opportunistic pathogen mainly causing infections in immunocompromised human patients or those with underlying chronic structural lung disease. Cases of disease in veterinary medicine remain scarce. Few animal species, including birds, are suspected of being vectors of the disease and there has not yet been a report of clinical disease in birds. We report the first case, to our knowledge, of systemic infection in a domestic bird. Case presentation. A female fiery-shouldered conure was submitted after death for necropsy following episodes of heavy breathing. The necropsy revealed multiple granulomatous lesions within the liver, air sacs and kidneys. Ziehl–Neelsen stains demonstrated the presence of numerous intralesional acid-fast bacilli. PCR assays and culture confirmed the presence of M. xenopi . Conclusion. Through this case we hope to describe the characteristics of M. xenopi disease in birds and the possible close relationship between animal and human infections.